2020
DOI: 10.1177/1479973120958428
|View full text |Cite
|
Sign up to set email alerts
|

CA 19-9 serum levels in patients with end-stage idiopathic pulmonary fibrosis (IPF) and other interstitial lung diseases (ILDs): Correlation with functional decline

Abstract: Idiopathic pulmonary fibrosis presents a progressive and heterogeneous functional decline. CA 19-9 has been proposed as biomarker to predict disease course, but its role remains unclear. We assessed CA 19-9 levels and clinical data in end-stage ILD patients (48 IPF and 20 non-IPF ILD) evaluated for lung transplant, to correlate these levels with functional decline. Patients were categorized based on their rate of functional decline as slow (n = 20; ΔFVC%pred ≤ 10%/year) or rapid progressors (n = 28; ΔFVC%pred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…Kodama T et al suggested that clinicians pay attention to evidence that elevated serum levels of CA19.9 may be related to poor prognosis in IPF patients [ 9 ]. Balestro et al recently reported CA 19-9 as a disease severity marker in patients with end-stage ILD, demonstrating an inverse correlation of this oncomarker with functional decline, particularly among patients with rapidly progressive IPF [ 7 ]. Ca15.3 has been studied in relation to the pathogenesis of IPF, and it has been associated with survival and disease severity, due to an inverse correlation between DLCO and high-resolution computed tomography (HRCT) findings [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kodama T et al suggested that clinicians pay attention to evidence that elevated serum levels of CA19.9 may be related to poor prognosis in IPF patients [ 9 ]. Balestro et al recently reported CA 19-9 as a disease severity marker in patients with end-stage ILD, demonstrating an inverse correlation of this oncomarker with functional decline, particularly among patients with rapidly progressive IPF [ 7 ]. Ca15.3 has been studied in relation to the pathogenesis of IPF, and it has been associated with survival and disease severity, due to an inverse correlation between DLCO and high-resolution computed tomography (HRCT) findings [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serum samples for assay of the following proteins/oncomarkers were drawn at baseline t0 and every 6 months of follow-up (6 months (t1), 12 months (t2), 18 months (t3), and 24 months (t4)): chitotriosidase (chitinase-1), carcinoembryonic antigen (CEA), cancer antigen 15-5 (Ca15-3), neuron-specific enolase (NSE), cancer antigen 19-9 (Ca19-9), cytokeratin fragment 21-1 (Cyfra 21.1), and cancer antigen 125 (Ca-125). Oncomarkers and chitotriosidase were assayed as previously reported [ 7 , 8 , 10 , 23 , 39 , 42 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…-Carbohydrate antigen 19-9 (CA 19-9): this glycoprotein produced by epithelium is a common gastrointestinal, mainly pancreatic, tumor biomarker. Its elevated levels in serum, have also been observed in benign respiratory diseases such as IPF and ILDs in general [25][26][27] .…”
Section: Peripheral Biomarkers Of Ipf and Lung Cancermentioning
confidence: 97%
“…By stratifying patient in terms of disease progression rate, Ca 19.9 level emerges as being inversely correlated to lung function decline, mainly in those patients who rapidly progress. Increased Ca 19.9 levels are associated with increased levels in the end-stage IPF, irrespective of treatment setting [ 106 ]. Indeed, fewer data are available on the potential role of circulating oncomarker levels in predicting response to therapy.…”
Section: Common Available Biomarkersmentioning
confidence: 99%